Effector Pt31812 from Puccinia triticina acts as avirulence factor for Lr42-mediated resistance in wheat - Li, Jianyuan; Li, Jiali; Wei, Jie; Li, Lin; Qi, Yue; Zhang, Yue; Yang, Wenxiang; Shen, Qian-Hua (Frontiers in Microbiology, 2025)
As an obligate biotrophic fungus, the leaf rust pathogen Puccinia triticina (Pt) secretes a repertoire of effector proteins into host cells for modulating plant immunity and promoting fungal pathogenesis. Here, we identify the Pt31812 effector and characterize its function in pathogenesis and immune-related activity in plants. In the study, Pt31812 was cloned by PCR, and the expression pattern and structure were analyzed by qRT-PCR and online softwares. Subcellular localization of Pt31812 was analyzed using transient expression on Nicotiana Benthamiana. Further functional analysis was conducted using transient expression and host-induced gene silencing (HIGS). The results showed that Pt31812 encodes candidate effector with a predicted signaling peptide (SP) at the N-terminus, and its expression was highly up-regulated during Pt infection of wheat. Subcellular localization analysis revealed that Pt31812 is localized in cytoplasm and nucleus when expressed in N. Benthamiana. Co-expression of Pt31812 and mammalian BAX protein revealed that Pt31812 inhibited BAX-induced cell death in N. Benthamiana, and the fragment of 22–88 aa from the N-terminus of the effector was important for the inhibiting activity. Interestingly, expression of Pt31812 in a panel of wheat differential lines with different Lr resistance genes showed that Pt31812 specifically triggered cell death in a Lr42-harboring wheat line. Furthermore, transient gene silencing of Pt31812 through BSMV-HIGS approach rendered loss of Lr42-mediated resistance against rust race Pt.-THSN and altered the infection type from resistant to susceptible. Our data reveal that Pt31812, as a candidate effector with immune inhibiting activity, acts as an avirulence determinant factor during Pt infection of Lr42-harboring wheat line. These findings highlight immune-related activity of specific Pt effectors and lay the foundation for further investigation into mechanisms of leaf rust fungal pathogenesis and recognition.